2011
DOI: 10.1029/2010ja016099
|View full text |Cite
|
Sign up to set email alerts
|

Global ionospheric response to nonmigrating DE3 and DE2 tides forced from below

Abstract: [1] In this paper we present the global spatial structure and seasonal variability of the COSMIC electron density response to the forced from below DE3 and DE2 tides during the period January 2008 to March 2009. The COSMIC electron density at fixed altitudes and SABER temperatures were utilized in order to define the ionospheric DE3 and DE2 tidal response to the DE3 and DE2 temperature tides coming from below. The tidal waves from both data sets have been extracted by the same data analysis method. The latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 55 publications
19
53
0
Order By: Relevance
“…The phases (not shown) in both datasets show that the migrating diurnal tide maximizes around 14 hours solar local time at all locations throughout the mid and low latitude area. These results are again indicative that the migrating diurnal tide in TEC reflects photoionization, consistent with the observations of Mukhtarov and Pancheva (2011) in F3/C electron density.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…The phases (not shown) in both datasets show that the migrating diurnal tide maximizes around 14 hours solar local time at all locations throughout the mid and low latitude area. These results are again indicative that the migrating diurnal tide in TEC reflects photoionization, consistent with the observations of Mukhtarov and Pancheva (2011) in F3/C electron density.…”
Section: Resultssupporting
confidence: 79%
“…Compared to the zonal mean and migrating diurnal tide, the migrating semidiurnal tide in TECs exhibits a clear bimodal (a) (b) structure in latitude, with peaks located roughly at 15° latitude in both hemispheres, consistent with the location of the EIAs. Mukhtarov and Pancheva (2011) suggested that a similar bimodal distribution observed in electron densities near 400 km is indicative of upwards coupling of the migrating semidiurnal tide in the MLT region via the equatorial fountain mechanism. The seasonal variation is again semiannual in nature with maxima (minima) in the postequinox (post-solstice) periods at the same times as those in the zonal mean and migrating diurnal tide.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations